Teaching Redemptively : bringing grace and truth into your classroom - Graham, Donovan L. (Colorado Springs, CO : Purposeful Design Publications, 2009)
"As God's image bearers, Christian teachers are called to reflect the character of our creative, redemptive God and to live according to His truth. This book encourages and challenges Christian teachers in any setting, public or private, secular or Christian, to teach redemptively--to employ biblical principles in all aspects of the educational process."-- p.4 of cover
Part 3: Redemptive teaching at work: building on norms and teaching with grace -- 21. A different kind of place: Omega Christian School -- 22. Curriculum design -- 23. Learning activities -- 24. Measurement, evaluation, and grading -- 25. Classroom behavior and discipline -- 26. The heart of a disciple maker: walking with God -- 27. Bringing it to life--individually and together
Includes bibliographical references (p. 287-289).
Keywords: Teaching -- Religious aspects -- Christianity; Christian teachers; Christian education -- Teaching methods; Christian education -- Aims and objectives; Learning -- Religious aspects -- Christianity